1971
DOI: 10.1111/j.1432-1033.1971.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enzymatically Catalyzed Mutarotation. The Mechanism of Action of Mutarotase (Aldose 1-Epimerase) from Escherichia coli

Abstract: 1. The free energy, enthalpy, and entropy of activation of the enzymatically catalyzed mutarotation of glucose have been determined: AG* 11.9 kcal/mol, AH* 12.8 kcal/mol, AS* 3.1 cal x mol-l x K-l. 2.The pH-dependence of the enzymatic activity has been investigated. The active center of the mutarotase from Escherichiu coli contains one functional group (pK 5.5) which in the dissociated form has only a catalytic function, and a second one (pK 7.6) which is responsible for the binding of the substrate.3. The bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…Within recent years, the enzyme from E. coli has been the subject of various biochemical analyses (1,8,9). These investigations have revealed that the enzyme requires neither bound metal ions nor cofactors for activity and that it functions as a monomer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within recent years, the enzyme from E. coli has been the subject of various biochemical analyses (1,8,9). These investigations have revealed that the enzyme requires neither bound metal ions nor cofactors for activity and that it functions as a monomer.…”
mentioning
confidence: 99%
“…These investigations have revealed that the enzyme requires neither bound metal ions nor cofactors for activity and that it functions as a monomer. A possible catalytic mechanism, first suggested by Hucho and Wallenfels (9), involves the abstraction of a proton from the 1Ј-hydroxyl group of the sugar by an enzymatic base while a side chain acidic group donates a proton to the C-5 oxygen. This results in cleavage of the ring, thereby yielding the open chain aldehyde.…”
mentioning
confidence: 99%
“…A possible catalytic mechanism for galactose mutarotase, first suggested by Hucho and Wallenfels (15) and outlined in Scheme 1, involves the abstraction of a proton from the C-1 hydroxyl group of the sugar by an enzymatic base and donation of a proton to the C-5 oxygen by a side chain acidic group thus resulting in ring cleavage. Subsequent rotation about the C-1/C-2 bond, followed by abstraction of the proton on the C-5 oxygen and donation of a proton back to the C-1 oxygen leads to product formation.…”
mentioning
confidence: 99%
“…Five highly conserved residues (Arg-71, His-96, His-170, Asp-243, and Glu-304) were within hydrogen-bonding distance to the hydroxyl groups of the bound galactose ligand. Previous kinetic studies suggested that the reaction mechanism for the enzyme proceeds via an acid/base mechanism with a transient ring opening (26,27), and the model of the mutarotase from L. lactis implicated Glu-304 as the likely catalytic base and either His-96 or His-170 as the catalytic acid (24). Accordingly, the reaction mechanism of galactose mutarotase is thought to occur via abstraction of the proton from the C-1 hydroxyl group by Glu-304 in the L. lactis enzyme and protonation of the ring oxygen of the sugar by His-170, which results in ring opening.…”
mentioning
confidence: 99%